Haemolytic anaemia in an HIV-infected patient with severe falciparum malaria after treatment with oral artemether-lumefantrine - Corpolongo, Angela (BioMed Central, 2012)
Intravenous (i.v.) artesunate is now the recommended first-line treatment of severe falciparum malaria in adults and children by WHO guidelines. Nevertheless, several cases of haemolytic anaemia due to i.v. artesunate treatment have been reported. This paper describes the case of an HIV-infected patient with severe falciparum malaria who was diagnosed with haemolytic anaemia after treatment with oral artemether-lumefantrine. The patient presented with fever, headache, and arthromyalgia after returning from Central African Republic where he had been working. The blood examination revealed acute renal failure, thrombocytopaenia and hypoxia. Blood for malaria parasites indicated hyperparasitaemia (6%) and Plasmodium falciparum infection was confirmed by nested-PCR. Severe malaria according to the laboratory WHO criteria was diagnosed. A treatment with quinine and doxycycline for the first 12 hours was initially administered, followed by arthemeter/lumefantrine (Riamet(®)) for a further three days. At day 10, a diagnosis of severe haemolytic anaemia was made (Hb 6.9 g/dl, LDH 2071 U/l). Hereditary and autoimmune disorders and other infections were excluded through bone marrow aspiration, total body TC scan and a wide panel of molecular and serologic assays. The patient was treated by transfusion of six units of packed blood red cell. He was discharged after complete remission at day 25. At present, the patient is in a good clinical condition and there is no evidence of haemolytic anaemia recurrence. This is the first report of haemolytic anaemia probably associated with oral artemether/lumefantrine. Further research is warranted to better define the adverse events occurring during combination therapy with artemisinin derivatives.